Essentials of forensic accounting - Crain, Michael A. (Michael Alan); Hopwood, William S.; Gendler, Richard S. (Wiley, 2019)
This book defines and explains the disciplined approaches to forensic accounting that lead to a thorough knowledge of the varied specialties within forensic accounting. Through illustrative examples and explanations, this book makes abstract concepts come to life for both seasoned professionals and students and it will help them understand and navigate successfully in this multifaceted area. It is an indispensable resource delivering matchless knowledge to practitioners, financial managers and students in understanding the complex elements and factors that impact the forensic accounting practice areas. This vital reference resource focuses the elements that must come together to effectively diminish the incidence and impact of fraudulent activities.